Intervenções por telefone para adesão ao exame colpocitológico - Lima, Thais Marques (2015)
The objective was to test the effects of behavioral and educational interventions by the phone on the adherence of women with an inadequate smear test periodicity. Therefore, we performed a quasi-experimental study comparing two groups: behavioral intervention (telephone reminder) and educational intervention ( educational session by the phone). The study was conducted at the Family Development Cente r (CEDEFAM) from January to August 2014. The studied population was composed of 524 women who underwent the Pap smear at the above-mentioned Center and their testi ng periodicity was not in compliance with the recommendations of the Ministry of Health. The sample population was selected according to the following criteria: women must hav e initiated their sexual activity, have an inadequate examination frequency, are aged between 25 and 64 years and have a mobile phone number recorded in their chart. The CAP (know ledge, attitude and practice) tool used in the investigation had been previously validated in an experimental study. Additionally, a socio-demographic data collection tool and an inter vention script made according to the principles of a Motivational Interview were also us ed. Data were analyzed using the Statistical Package for Social Sciences (SPSS), ver sion 20.0. The data showed that almost the entire sample (98.1%) had heard about prevention of cervical cancer, but 68.7% had an inadequate knowledge of the test. It was found that the average time since the last examination was 31.7 months and the main reason for the inadequate periodicity was the difficulty in scheduling an appointment (40.8%). Th e comparison of their knowledge, attitude and practice before and after the behavioral and ed ucational interventions showed that there was a statistically significant change (p = 0.0283) in the knowledge of women who participated in the educational intervention, there was no proven change in the attitude of women of either group, and there was a significant change toward an increased adherence to the Pap smear in both groups (p < 0.0001), with the women who participated in the behavioral group showing a greater adherence (66.8%). Only the knowledge of the proper goal of the Pap smear was statistically associated with the knowled ge, attitude and practice of the test (p <0.05). Knowledge and attitude were statistically a ssociated with the women having a previous experience with any educational cervical c ancer prevention activity. A history of cancer of any origin in the family was associated w ith the knowledge and practice of the test. With regard to practice, educational level, marital status and the presence of a chronic disease were factors significantly associated with it. From the observed changes we can conclude that the different interventions were effective in incre asing smear test compliance among women, confirming the initial hypothesis. Therefore, it is important for the nursing professionals to conduct permanent health education activities aimed to promote the prevention of cervical cancer